Des femmes font sécession. Récits de vies et itinéraires amoureux de féministes et lesbiennes des années 1970 - Françoise Flamant (Genre, Sexualité et Société)
In 2007 Françoise Flamant published a book titled A tire d’elles. Itinéraires de féministes radicales des années 1970, in which she collects the testimonies of women engaged in the Liberation Movement, who identified with both feminist and lesbian political struggles. She gives here an account of her history and analyses these movements. She shows the complexity of individual trajectories and the extreme richness of the political experiences in the 70s, she and her comrades developed: communal life, exile, writing. Also reexamining the theoretical context of their political engagement and their ideological bricolage, Flamant insits on the importance of leading theorists, from Simone de Beauvoir to Monique Wittig, but also Herbert Marcuse who was translated by Wittig herself.